Large signal analysis of Mach-Zehnder modulator intensity response in a linear dispersive fiber - J. M. B. Oliveira (2006)
Two novel theoretical models that give the intensity of the optical signalgenerated by a Mach-Zehnder modulator through a dispersive medium are reported.These models include the chirp and dispersion factors and can be used for largesignalsand for large values of the chirp parameters. Theoretical results are in goodagreement with the simulation.